INICJATYWY RADY EUROPY I KOMISJI EUROPEJSKIEJ NA RZECZ WSPIERANIA REFLEKSYJNOŚCI NAD PROCESEM UCZENIA SIĘ I NAUCZANIA JĘZYKA OBCEGO - Jedynak, Małgorzata (Neofilolog, 2019)
In the era of globalisation a command of foreign languages is regarded as a priority. For this reason, the Council of Europe and the European Commission promote language learning and linguistic diversity. A focal point in their language policy is reflection, which is recognized as a key feature of an employee’s professionalism. Therefore, the importance of reflection is stressed throughout all the years of language education. The objective of this paper is to give information about the documents, tools and actions which support a reflective approach to language learning and teaching in Europe.